Non-intrusive monitoring of everyday behavioral activities in an indoor environment - Arshad, Atika; Khan, Sheroz; Zahirul Alam, A. H. M.; Tasnim, Rumana (University of Electronic Science and Technology of China, 2016)
A non-intrusive design for monitoring everyday activities of an elderly person is presented. The proposed system is intended to be used in the bedroom, allowing the elders to stay at home in a safe environment. The required hardware design is simple in structure and cost effective. The sensor design is implemented by using capacitive sensors and an Arduino microcontroller unit. And a real time graphical user interface is implemented to monitor the elderly person. The performance analysis shows that the sensor design is able to differentiate between a human body and a house pet